Sustainability in the Public Sector: A study into the progress being made by local government to engrain sustainable development principles into the heart of strategy - Powell, Sonja (2010)
This report explores the state of sustainability in local government including the progress being made to embed sustainable development principles into the heart of strategy, and motivating factors and barriers to sustainable development in local government.